MEMBANGUN BADAN PUBLIK YANG TRANSPARAN DAN AKUNTABEL DENGAN MEMBUDAYAKAN KESADARAN BERKONSTITUSI - Sukriono, Didik (JURNAL KONSTITUSI, 2011)
Substitution for several times of national and local leader, which should to became historical momentum to well held of social arrangement, economic arrangement, and better new political arrangement. But exactly on the contrary that is tending the increasing of " KKN, destabilizes, symptom of separatism and terror " later on very is having an in with of governmental performance obsolesce and "gnaw" top kick regime legitimacy which is selected democratically. Governmental performance obsolesce in context service of public, look at pattern management of less responsive service, less informative, less accessible, less coordination, tend to bureaucratically, do not want to hear sigh, suggestion and criticism, and inefficient. While from human resource (SDM), look the lack of professionalism, competence, ethics and empathy. Therefore grow to develop conscious culture have constitution to represent undoubtedly. Its meaning if society have comprehended elementary norms in constitution and applying it in life of nation and state, hence can be ascertained to know and can maintain constitutional rights of him which is guaranteed in UUD 1945. Besides, society can participate fully to execution of UUD 1945 either through execution of his or its rights and obligations as citizen, participating in management of governance and state, and also earn also control to management of state and the way governance. The condition by itself will prevent the happening of deviation and or mistaken of constitution